MIXTILINEAR EXCIRCLE ON THE ANGLE TRISECTOR OF A TRIANGLE - Fionari, Gebi; Mashadi, Mashadi; Syafitri, sukma Novia (Jurnal Matematika UNAND, 2025)
The most famous theorem on the angle trisector of a triangle is Morley’s theorem, namely the existence of an equilateral triangle formed from the trisector of its three angles. In this article, the mixtilinear excircle concept will be developed for triangles formed by constructing angle trisectors in a triangle. The results obtained will be expressed in the form of a theorem which states the ratio of several mixtilinear excircles whose value is equal to one. Apart from that, the ratio of several mixtilinear excircles can also be expressed in tangen form of the angles formed.